Transient Loss of Protection Afforded by a Live Attenuated Non-typhoidal Salmonella Vaccine in Mice Co-infected with Malaria. - Jason P Mooney; Seung-Joo Lee; Kristen L Lokken; Minelva R Nanton; Sean-Paul Nuccio; Stephen J McSorley; Renée M Tsolis (Public Library of Science (PLoS), 2015)
In immunocompetent individuals, non-typhoidal Salmonella serovars (NTS) are associated with gastroenteritis, however, there is currently an epidemic of NTS bloodstream infections in sub-Saharan Africa. Plasmodium falciparum malaria is an important risk factor for invasive NTS bloodstream in African children. Here we investigated whether a live, attenuated Salmonella vaccine could be protective in mice, in the setting of concurrent malaria. Surprisingly, mice acutely infected with the nonlethal malaria parasite Plasmodium yoelii 17XNL exhibited a profound loss of protective immunity to NTS, but vaccine-mediated protection was restored after resolution of malaria. Absence of protective immunity during acute malaria correlated with maintenance of antibodies to NTS, but a marked reduction in effector capability of Salmonella-specific CD4 and CD8 T cells. Further, increased expression of the inhibitory molecule PD1 was identified on memory CD4 T cells induced by vaccination. Blockade of IL-10 restored protection against S. Typhimurium, without restoring CD4 T cell effector function. Simultaneous blockade of CTLA-4, LAG3, and PDL1 restored IFN-γ production by vaccine-induced memory CD4 T cells but was not sufficient to restore protection. Together, these data demonstrate that malaria parasite infection induces a temporary loss of an established adaptive immune response via multiple mechanisms, and suggest that in the setting of acute malaria, protection against NTS mediated by live vaccines may be interrupted.